Influence of diverse natural biopolymers on the physicochemical characteristics of borage seed oil-peppermint oil loaded W/O/W nanoemulsions entrapped with lycopene. (6th October 2021) - Rehman, Abdur; Tong, Qunyi; Korma, Sameh A; Han, Wen; Karim, Aiman; Sharif, Hafiz Rizwan; Ali, Ahmad; Yaqoob, Sanabil; Khalifa, Salah A; Cacciotti, Ilaria
Abstract: Borage seed oil (BSO), peppermint oil (PO) and lycopene (LC) have accomplished a lot of interest due to their therapeutic benefits in the food and pharmaceutical sectors. However, their employment in functional food products and dietary supplements is still precluded by their high susceptibility to oxidation. Thus, the encapsulation can be applied as a promising strategy to overcome these limits. In the present study, doubly layered water/oil/water (W/O/W) nanoemulsions were equipped using purity gum ultra (PGU), soy protein isolate (SPI), pectin (PC), whey protein isolate (WPI) and WPI-PC and SPI-PC complexes, and their physico-chemical properties were investigated. Our aim was to investigate the influence of natural biopolymers as stabilizers on the physicochemical properties of nanoemulsified BSO, PO and lycopene thru W/O/W emulsions. The droplet size of the fabricated emulsions coated with PGU, WPI, SPI, PC, WPI-PC, and SPI-PC was 156.2, 265.9, 254.7, 168.5, 559.5 and 656.1 nm, correspondingly. The encapsulation efficiency of the entrapped bioactives for powders embedded by PGU, WPI, SPI, PC, WPI-PC, and SPI-PC was 95.21%, 94.67%, 97.24%, 92.19%, 90.07% and 92.34%, respectively. In addition, peroxide and p-anisidine values were used to measure the antioxidant potential of the entrapped bioactive compounds during storage, which was compared to synthetic antioxidant and bare natural antioxidant. The collected findings revealed that oxidation occurred in oils encompassing entrapped bioactive compounds, but at a lower extent than for non-encapsulated bioactives. In summary, the findings obtained from current research prove that the nanoencapsulation of BSO surrounded by innermost aqueous stage of W/O/W improved its stability as well as allowed a controlled release of the entrapped bioactives. Thus, the obtained BSO-PO-based systems could be successfully used for further fortification of food-stuffs.